Developing digital module for human literacy and technology literacy - Dody Hartanto; Puguh Wahyu Prasetyo; Ika Maryani; Ega Asnatasia Maharani; Intan Puspitasari; Diah Asta Putri; Oktira Roka Aji; Wachid Eko Purwanto (Universitas Ahmad Dahlan, 2020)
In the era of industrial revolution 4.0, many human activities depend on the gadget and the internet connection. We can observe the daily activities of human life right now. When they wake up in the morning, they usually start by using their handphones or gadget. This condition motivates educators to build a digital module in order to use the positive point of view of the Industry Revolution 4.0 era. In this chance, the researchers develop two topics that are very important for human life in Industry Revolution 4.0, whicht are, human literacy and technology literacy. Both of the topics were derived into two-courses. The course of development of students (Perkembangan Peserta Didik) will be representing the human literacy topics and the course of introduction to Biotechnology (pengantar bioteknologi) will be representing the technology literacy topic. The research is research and development. Furthermore, the products of this research are flipbooks that were uploaded on the Learning Management System managed by Universitas Ahmad Dahlan.